SOSIALISASI PROGRAM STUDI S1 FKIP UNITOMO DI MAN 9 JOMBANG - Setiawan, Windi; Prastiwi, Lusiana; Amrullah, Imron; Huda, Nuril; Hatip, Ahmad; Haerussaleh, Haerussaleh (Jurnal Pengabdian Masyarakat Khatulistiwa, 2024)
ABSTRACTThe importance of higher education plays an important role in every individual's career in the future. This step needs to be considered carefully since students are in high school. They have the freedom to decide after graduation to determine their next steps. Are they working, studying, or working while studying? This question is something that always arises when they are about to graduate. This was also found in students at MAN 9 Jombang. Most of them still have minimal information about higher education. The Community Service Team (abdimas) was present to answer this problem through the Socialization activities of the FKIP Unitomo Undergraduate Study Program at MAN 9 Jombang. This activity is carried out in three stages. First, the planning stage. At this stage the researcher coordinates with the school and determines the material to be presented. Second, the implementation stage. At this stage, the community service team carried out socialization which was attended by all grade 12 students in the MAN 9 Jombang hall. At the reflection stage, the community service team provides the opportunity to conduct questions and answers with students. As a result of this activity, students have information regarding the registration mechanism, graduate profiles, various academic activities, and student achievements in mathematics education and Indonesian language and literature education study programs.Keywords: socialization, study program, madrasah, senior high school ABSTRAKPentingnya pendidikan tinggi memegang peranan penting bagi karir setiap individu di kemudian hari. Langkah tersebut perlu dipikirkan secara matang sejak siswa duduk di bangku SMA. Mereka memiliki kebebasan untuk menentukan setelah lulus untuk menentukan langkah selanjutnya. Apakah mereka bekerja, kuliah, atau bekerja sambil kuliah? Pertanyaan ini menjadi hal yang senantiasa muncul saat mereka hendak lulus. Hal ini juga dijumpai pada siswa di MAN 9 Jombang. Sebagian besar dari mereka masih minim informasi tentang perguruan tinggi. Tim pengabdian Masyarakat (abdimas) hadir untuk menjawab permasalahan tersebut melalui kegiatan Sosialisasi Program Studi S1 FKIP Unitomo di MAN 9 Jombang. Kegiatan ini dilakukan melalui tiga tahap. Pertama, tahap perencanaan. Pada tahap ini peneliti melakukan kordinasi dengan pihak sekolah dan menentukan materi yang akan disampaikan. Kedua, tahap pelaksanaan. Pada tahap ini, tim abdimas melakukan sosialisasi yang dihadiri oleh seluruh siswa kelas 12 di aula MAN 9 Jombang. Pada tahap refleksi, tim abdimas memberikan kesempatan untuk melakukan tanya jawab dengan siswa. Hasil dari kegiatan ini, siswa memiliki informasi terkait mekanisme pendaftaran, profil lulusan, berbagai kegiatan akademik, dan prestasi mahasiswa prodi pendidikan matematika dan pendidikan Bahasa dan sastra Indonesia.Kata Kunci: sosialisasi, program studi, madrasah, sekolah menengah atas